The association of sexual minority status and bullying victimization is modified by sex and grade: findings from a nationally representative sample - Junjie Lu; Jiarui Yang; Ekaterina Sadikova; Henning Tiemeier (BMC Public Health, 2024)
Abstract Background Sexual minority status is associated with face-to-face bullying and cyberbullying victimization. However, limited studies have investigated whether such a relationship differs by sex or grade in a nationally representative sample. Methods We concatenated the national high school data from the Youth Risk Behavior Surveillance System (YRBSS) chronologically from 2015 to 2019, resulting in a sample of 32,542 high school students. We constructed models with the interaction term between sexual minority status and biological sex assigned at birth to test the effect modification by sex on both the multiplicative and additive scales. A similar method was used to test the effect modification by grade. Results Among heterosexual students, females had a higher odds of being bullied than males, while among sexual minority students, males had a higher odds of being bullied. The effect modification by sex was significant on both the multiplicative and additive scales. We also found a decreasing trend of bullying victimization as the grade increased among both heterosexual and sexual minority students. The effect modification by the grade was significant on both the multiplicative and the additive scale. Conclusions Teachers and public health workers should consider the difference in sex and grade when designing prevention programs to help sexual minority students.